The case for a Themis asteroid family spacecraft mission. (March 2022) - Landis, M.E.; Castillo-Rogez, J.C.; Hayne, P.O.; Hsieh, H.; Hughson, K.H.G.; Kubitschek, D.; Miller, K.E.; Prettyman, T.H.; Rivkin, A.S.; Schmidt, B.E.; Scully, J.E.C.; Yamashita, N.; et al.
Abstract: The last decade has highlighted the importance of icy asteroids as likely outer-solar-system planetesimals that brought organics and ices to the inner solar system. Better characterizing the relationship between these objects and other water-rich bodies throughout the solar system and their evolution as potential sources of organics has broad-ranging implications. Additionally, characterizing ice-rich bodies is important for understanding the evolution and diversity of Ocean Worlds. Observations and modeling have suggested that the Themis asteroid family likely represents the fragments of an icy protoplanet originally similar in size to (10) Hygeia (∼444 ​km), which was broken apart by a catastrophic collision and with (24) Themis possibly representing its core. While extensive observations have been made of the icy asteroid (1) Ceres, exploring the deep interior structure and processes is difficult when observing an intact planetary body. Thus, the many objects in the Themis family provide an opportunity to observe an interior cross-section of one of these protoplanetary objects. The Themis family contains a variety of members, including multiple Main Belt Comets (e.g., 133P/Elst-Pizarro) for which comet-like dust ejection (consistent with being driven by sublimation of volatile material) has been observed. In this paper, we present the science case for why the exploration of the Themis family is key to understanding icy objects in the solar system, and present three design-referenced mission architectures that would be plausible under the NASA Discovery mission cost cap that would address key science objectives pertaining to icy asteroids. Highlights: The Themis family records the internal processes of a large, icy parent body. A mission to (24) Themis and a Main Belt Comet is feasible under the NASA Discovery program. A (24) Themis orbiter would maximize science return.